2013
DOI: 10.1038/cdd.2013.62
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-199a is induced in dystrophic muscle and affects WNT signaling, cell proliferation, and myogenic differentiation

Abstract: In patients with Duchenne muscular dystrophy (DMD), the absence of a functional dystrophin protein results in sarcolemmal instability, abnormal calcium signaling, cardiomyopathy, and skeletal muscle degeneration. Using the dystrophin-deficient sapje zebrafish model, we have identified microRNAs (miRNAs) that, in comparison to our previous findings in human DMD muscle biopsies, are uniquely dysregulated in dystrophic muscle across vertebrate species. MiR-199a-5p is dysregulated in dystrophindeficient zebrafish,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 59 publications
8
108
0
2
Order By: Relevance
“…The results of previous studies have also indicated that miR-199a-5p could target several factors that regulate cell proliferation within the WNT signaling pathway, including FZD4 and WNT2 (Alexander et al 2013). Our data provide new evidence that miR-199a-5p plays a dominant role in GC-inhibited osteoblast proliferation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The results of previous studies have also indicated that miR-199a-5p could target several factors that regulate cell proliferation within the WNT signaling pathway, including FZD4 and WNT2 (Alexander et al 2013). Our data provide new evidence that miR-199a-5p plays a dominant role in GC-inhibited osteoblast proliferation.…”
Section: Discussionsupporting
confidence: 72%
“…Shi et al (2014a,b) showed that miR-199a-5p affects porcine preadipocyte proliferation and differentiation. Alexander et al (2013) found that miR-199a-5p affects WNT signaling, cell proliferation, and myogenic differentiation. Furthermore, lentivirus-mediated overexpression of miR199a-5p has been shown to inhibit cell proliferation in human hepatocellular carcinoma (Xu et al 2012a,b).…”
Section: Discussionmentioning
confidence: 99%
“…others have profiled dysregulated microRNAs from 3 dystrophindeficient species (human, mouse, and zebrafish), and identified common microRNAs with a unique biosignature for the diseased state (35,85,86). Profiling of several of these microRNAs, including the muscle-enriched miR-1, miR-133a, and miR-206, have been shown as useful serum biomarkers in dystrophic mice (87).…”
Section: Dock3 Is An Essential Regulator Of Pten/akt and Rac1 Signalimentioning
confidence: 99%
“…For example, in patients with muscular defects, such as myopathies and atrophy, WNT/␤-catenin signaling is most likely altered due to a genetic and/or epigenetic cause(s) (80). Our results highlight that WNT/␤-catenin signaling is a widely used mechanism in skeletal muscles which regulate stepspecific targets during myogenesis.…”
Section: Discussionmentioning
confidence: 78%